Bacteriologic Profile and Antibiotic Susceptibility in Patients with UTIs in Tertiary Care Hospital - Fatima, Ambreen; Fasih, Fatima; Naseem, Saima; Sajjad, Mehwish; Gohar, Hareem; Bukhari, Uzma (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVES: To evaluate the bacteriological profile and antibiotic susceptibility in patients with urinary tract infections. METHODOLOGY: This retrospective study with a cross-sectional design was held at Dow University of Health Sciences, Karachi; we evaluated records of patients from January to December 2020 at the Department of Microbiology, Dow Diagnostic Reference and Research Laboratory, Karachi, who requested urine culture due to urinary tract infection. Details such as the most common bacteria, specific antibiotic susceptibility and resistance with all demographic information were recorded. RESULTS: A total of 57785 samples were collected, of which 19620 were positive. The highest bacterial contaminations of the urinary region were detected among Females. E.coli remains a dominant pathogen that affects all age groups and genders, followed by Klebsiella, Acinetobacter, Enterobacter and Proteus. The most resistant drugs observed in our study were cefixime and cefuroxime, followed by ampicillin and Cotrimoxazole. The most sensitive and minor resistant drug against isolates is Colistin, followed by Amikacin and nitrofurantoin. CONCLUSION: It is among the studies with significant findings and delivers essential data regarding bacterial trends. Current research can be compared with other studies for antimicrobial susceptibility approaches of pathogens and helps us decide on empirical treatment of UTIs. Parallel analysis should be designed on a large scale in diverse areas and regions, forming empiric antibiotic therapy guidelines according to the local antimicrobial susceptibility pattern, which helps improve patient outcomes and unjudicial antibiotic use. KEYWORDS: Urinary infections, Uro-pathogens, antibiotic resistance and sensitivity